HIGH PRODUCTION OF JAVA SOCKETS (HPJS) FOR HELTH CLOUDS IN SCIENCE - Melnyk, Vasyl; Zhyharevych, Oksana; Melnyk, Kateryna (Proceedings of National Aviation University (archive), 2015)
Computer clouds are using in health science for its data collections, manipulations and providing security needs in communications to exchange. The clouds distribution data character is using in science applications created to evaluate the data of the health-care. The science programs like medical visualization, genetic and protein conclusions, map-drag therapy and clinical decisions systems of support (CDSS) require high performance messaging libraries with minimum computer and communication spends and the effective utilization of the resources. The highperformance Java sockets (HPJS) encapsulate the needs of message high communications between cloud platforms science applications. HPJS effectively uses the Java socket realization for high-performance inner-process communications. With single-copy protocol, re-usability of the thread and communication overhead reduction, HPJS can use the message exchange in two times quickly to conventional buffered communication libraries.